Internalisasi Nilai-Nilai Akhlak Karimah Melalui Kegiatan Pencak Silat di Pondok Pesantren Annuqayah Latee - Zainurrahman, Ahmad; Hariva, Zayyana (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
Indonesia is currently confronting a serious moral crisis, marked by a persistent increase in moral degradation among youth and students. Pencak silat, a traditional Indonesian martial art, integrates physical, spiritual, and moral dimensions, making it a potentially effective vehicle for character formation. Islamic boarding schools (pesantren) have strategically incorporated pencak silat as an instrument for moral development among their students. This study aims to examine (1) the process of moral value internalization through pencak silat activities, and (2) the impact of such internalization on students' moral conduct at Annuqayah Latee Islamic Boarding School. Grounded in Peter L. Berger's social construction theory, this study employs a qualitative field research design. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using Miles and Huberman's interactive model, comprising data reduction, data display, and conclusion drawing/verification. The findings reveal that moral value internalization is enacted through narrative and philosophical instruction, role modeling and mentorship, as well as habituation and practical application in daily life. Furthermore, this internalization process demonstrably enhances students' emotional resilience, self-regulation, and prosocial behavior. These findings suggest that pencak silat, when embedded in a structured Islamic educational environment, constitutes an effective pedagogical strategy for holistic moral development.